Banana Peel Adsorbent to Reduce the Concentration of Lead and Cadmium Metal Pollution in Landfill Leachate - Sri Milawati; Adhitiyawarman Adhitiyawarman; Rossie Wiedya Nusantara (Jurnal Kimia Sains dan Aplikasi, 2024)
Banana peels can be a valuable adsorbent for reducing heavy metals in water. This study investigated the effect of chemical activators on Nipah banana peel (Musa acuminata balbisiana) on their ability to reduce Pb and Cd metals in landfill leachate. Before the adsorption test, the banana peels were treated with a different chemical activator, including detergent, NaOH, KOH, and H3PO4. The results showed that H3PO4 adsorbs relatively high amounts of metals (Pb-75.800%, Cd-18.491%) in landfill leachate among these activators. FTIR analysis showed that banana peels treated with H3PO4 produced sharper carbonyl or carboxyl group peaks. These groups are very influential in the metal adsorption process. SEM-EDS analysis of the H3PO4-treated banana peels showed an increase in carbon and oxygen elements in the banana peels and changes in the pore surface that enhanced the adsorption process on Pb and Cd metals. From this study, banana peels activated with H3PO4 showed great potential to be developed into adsorbents to reduce heavy metal concentration.